The relationship between anthropometric features and dynamical-statical balance - Yazici, A. G.; Yildiz, K. (Journal of Sports Medicine & Doping Studies, 2019)
Aim: This study aims that searching whether hemispheric differences do any effects into dynamical-statical balance levels and anthropometric features or not on the spotters who had active sport-life.